PENGARUH MEDIA FLASH CARD TERHADAP PENGUASAAN KOSAKATA BAHASA INGGRIS SISWA KELAS IV SD - Mitami Mitami; Nurul Muttaqien; Ino Budiatman (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This study aims to determine the effect of using Flash Card media on English vocabulary mastery in grade IV at SDN Pegadungan 02 Pagi. This study used a quantitative experimental approach with the Quasi-Experimental Design type of Nonequivalent Control Group Design. The population in this study were 120 students in class IV at SDN Pegadungan 02 Pagi with a sample of 60 students in two classes divided into 30 students in class IV A as the control class and 30 students in class IV C as the experimental class. The data collection technique used a test (pretest and posttest) of English vocabulary in the form of short entries totaling 10 questions. This research was tested and analyzed with the help of SPSS. In the independent sample t-test posttest test, the sig value was obtained. (2 - tailed) 0.009 <0.05 which shows that there is an effect of using Flash Card media on English vocabulary mastery. The average posttest score for the experimental class was 82 and 71.67 for the control posttest class. This shows that the use of Flash Card media increases students' vocabulary mastery more significantly